2014
DOI: 10.1007/s13311-014-0301-2
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic Encephalopathies: New Genes and New Pathways

Abstract: Epileptic encephalopathies represent a group of devastating epileptic disorders that occur early in life and are often characterized by pharmaco-resistant epilepsy, persistent severe electroencephalographic abnormalities, and cognitive dysfunction or decline. Next generation sequencing technologies have increased the speed of gene discovery tremendously. Whereas ion channel genes were long considered to be the only significant group of genes implicated in the genetic epilepsies, a growing number of non-ion-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(29 citation statements)
references
References 150 publications
(162 reference statements)
0
27
0
Order By: Relevance
“…Early infantile epileptic encephalopathies (EIEEs) are a heterogeneous group of severe epilepsies with multiple seizure types beginning in infancy with a poor motor and cognitive prognosis …”
mentioning
confidence: 99%
“…Early infantile epileptic encephalopathies (EIEEs) are a heterogeneous group of severe epilepsies with multiple seizure types beginning in infancy with a poor motor and cognitive prognosis …”
mentioning
confidence: 99%
“…M-channels are variable in terms of tetramer subunit composition [118, 119], which also can involve contributions from Kv7.5 [120]. Mutations in Kv7.2 or Kv7.3 can result in a form of epilepsy known as benign familial neonatal convulsions (BFNC) [121123], as well as more severe epileptic encephalopathy [124]. Kv7.4 is expressed in the neurons of the auditory pathway and in the inner ear; loss-of-function mutations are associated with progressive hearing loss [121, 123, 125].…”
Section: Kv7 Channels and Diseasementioning
confidence: 99%
“…It is estimated that between 1% and 10% of childhood epilepsies are a result of this syndrome 6. Previous data have suggested that only approximately 10% of LGS patients have seizures that are fully controlled with medication therapy 7.…”
Section: Introductionmentioning
confidence: 99%